Development of Plants and Animals Puppet Media Based on Conservation Values in Learning to Write Creative Drama Scripts in Elementary Schools - Hamidulloh Ibda (Southeast Asian Journal of Islamic Education, 2019)
This research is motivated dissatisfaction of teachers and students on learning media in school. The purpose of this study is (1) describe the development needs of plants and animals puppet media, (2) determining the value of the puppet characters of plants and animals, (3) describe the use of plants and animals puppet media, (4) test the effectiveness of the use of plants and animals puppet media. The method used is Research and Development (R & D). The eight stages covering explore the potential and problems, analyze the needs, preparation of media design, media validation, revision, testing a limited scale, revision back, and wide-scale trials. The results of this study indicate that (a) the needs of the media by the learner, including packaging, contents, materials, physical, and values contained in the media; (B) the character of the value of plants and animals puppet media is conservation values; (C) the utilization of plants and animals puppet media carried out in groups with one group consists of 2-3 people; (D) the development of plants and animals puppets charged effective conservation for students fifth grade elementary school.